Education of disaster using gamification technique - Mohamad Zahir, Noreliaezani; Chong, Khai Lin (Universiti Utara Malaysia, 2020)
Natural disaster always happens and is an increasing phenomenon that affecting people globally. Disaster is the tragedy of a natural or human-made hazard, where the hazard is a situation which poses a level of threat to life, health, property, or environment that negatively affects society or environment. Therefore, the purpose of this study is to know the effectiveness of education of disaster among children using the gamification technique. By using a quantitative research method, the data is collected through the questionnaire. The respondent involved 28 students, consist of standards 4 and 5 from SK Felda Bukit Tangga. The data from this study is analyzed using SPSS. All the data have been analyzed with descriptive analysis only. Future research needs to involve more respondents to enrich the data and maybe can use another test of data to produce more accurate results.